Effect of supplementing a multi-carbohydrase enzyme complex to corn–soy-based diets on growth performance, intestinal digesta viscosity, and carcass traits of broiler chickens - H. Leyva-Jimenez; Y. Burden; C. Soto; K. McCormick; A. Woodward; B. Dirks (Journal of Applied Poultry Research, 2024)
SUMMARY: Poultry feed could represent 70% of the total production costs and with the constant increase in feedstuffs prices; there is a big interest in reducing the cost of feed globally. The use of multi-carbohydrase enzymes (MCE) to increase the nutritional value of ingredients by reducing the harmful effects of nonstarch polysaccharides could represent significant cost savings for the poultry industry. Thus, the present study was conducted to evaluate the effect of supplementing MCE to corn–soybean meal-based diets. The study consisted of a complete randomized block design of 5 treatments, positive control (PC), negative control (NC; −125 kcal/kg ME compared with the PC), and the NC + MCE at 75 (MCE75), 100 (MCE100), and 125 (MCE125) ppm. The basal diets were supplemented with a 6-phytase at 1,000 FTU/kg. The feeding program consisted of 3 dietary phases (starter 0–14 d; grower 14–28 d; finisher 28–42 d). Cumulatively after 42 d, the NC diet decreased (P = 0.003) the BW of the chickens when compared to PC and MCE125. The NC group resulted in increased (P < 0.001) FCR compared to all other treatments. When the FCR was adjusted to a common weight (2.94 kg), the MCE-treated groups were not different (P > 0.05) from the PC. Breast yield increased linearly (P = 0.008) with increasing dietary inclusion levels of MCE. The NC group tended (P = 0.059) to increase digesta viscosity compared to PC and MCE125. The supplementation of MCE to energy-reduced broiler diets maintained growth performance and showed positive effects to improve breast yield.